2022
DOI: 10.1101/2022.10.27.514065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The small non-coding RNA B11 regulates multiple facets ofMycobacterium abscessusvirulence

Abstract: Mycobacterium abscessuscauses severe, virtually incurable disease in young patients with cystic fibrosis. Little is known inM. abscessusabout the roles of small regulatory RNAs (sRNA) in gene expression regulation. Here, we show that the sRNA B11 controls gene expression and virulence-associated phenotypes in this pathogen. B11 deletion from the smooth strain ATCC_19977 produced a rough colony morphology, increased pro-inflammatory signaling and virulence in in-vivo infection models, and increased resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 72 publications
0
4
1
Order By: Relevance
“…Here, we explored the biological function and regulatory mechanisms of sRNA B11 in M. marinum . By using different methods to discover B11-targets, we found that B11 controls several key genes in the LOS biosynthesis locus, which is distinct from the regulatory roles reported for B11 orthologues in M. smegmatis and M. abscessus (26,27). Furthermore, we found that M. marinum strains lacking B11 display a clear colony phenotype, suggesting that B11 acts as a negative posttranscriptional regulator of LOS synthesis.…”
Section: Introductioncontrasting
confidence: 61%
See 4 more Smart Citations
“…Here, we explored the biological function and regulatory mechanisms of sRNA B11 in M. marinum . By using different methods to discover B11-targets, we found that B11 controls several key genes in the LOS biosynthesis locus, which is distinct from the regulatory roles reported for B11 orthologues in M. smegmatis and M. abscessus (26,27). Furthermore, we found that M. marinum strains lacking B11 display a clear colony phenotype, suggesting that B11 acts as a negative posttranscriptional regulator of LOS synthesis.…”
Section: Introductioncontrasting
confidence: 61%
“…Our data showed that the seed region for regulatory base pairing by B11 is a cytosine-rich loop near its 3' end, which appears to be conserved in the B11 orthologues in M. smegmatis (26) and M. abscessus (27). Because mycobacteria have high GC-content with numerous guanine-rich motifs throughout the entire genome, computational methods using the cytosine-rich regions to predict the targets were not accurate.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations